A sustainable fertilization strategy to boost maize yield and photosynthetic resilience in saline soils - Zhou, Hui; Guo, Jiawei; Wang, Yongqiang; Wang, Jian; Liu, Hu (Frontiers in Plant Science, 2025)
IntroductionSoil salinization is a major constraint to crop production in arid and semi-arid regions. Combined application of organic and inorganic nitrogen (OIN) has been recognized as an effective strategy to improve productivity in saline soils. However, mechanisms underlying yield improvement related to photosynthesis and antioxidant responses remain unclear.MethodsA field experiment was conducted from 2018 to 2020 in the Hetao Irrigation District of Inner Mongolia using mildly saline soil (S1, EC = 0.68 dS m⁻¹) and moderately saline soil (S2, EC = 1.25 dS m⁻¹). Six nitrogen treatments were applied: no nitrogen (CK), inorganic nitrogen only (U1), and organic nitrogen replacing 25%, 50%, 75%, and 100% of inorganic nitrogen (U3O1, U1O1, U1O3, and O1). Maize growth, photosynthetic parameters, and antioxidant enzyme activities were measured.ResultsUnder S1 conditions, OIN significantly enhanced leaf area index (LAI), photosynthetic performance, superoxide dismutase (SOD) activity, and yield, with U1O1 yielding the highest production. Under S2 conditions, growth and photosynthesis were reduced, while malondialdehyde (MDA) content and antioxidant enzyme activities increased. OIN application improved growth, photosynthesis, and catalase (CAT) activity, with O1 achieving the highest yield. Structural equation modeling indicated that yield improvement in S1 was mainly driven by photosynthetic traits, whereas in S2 it resulted from combined effects of growth, photosynthesis, and CAT activity.DiscussionOverall, OIN application mitigates salinity stress effects on maize, with U1O1 optimal for mildly saline soil and O1 optimal for moderately saline soil. These findings provide insights into managing nitrogen forms to improve crop productivity in saline environments.